2009
DOI: 10.1158/1535-7163.mct-08-0534
|View full text |Cite
|
Sign up to set email alerts
|

Vorinostat and bortezomib exert synergistic antiproliferative and proapoptotic effects in colon cancer cell models

Abstract: Despite the availability of several Food and Drug Administration-approved drugs, advanced inoperable colorectal cancer remains incurable. In this study, we focused on the development of combined molecular targeted therapies against colon cancer by testing the efficacy of the combination of the histone deacetylase inhibitor vorinostat with the proteasome inhibitor bortezomib to determine if this resulted in synergistic antitumor effects against colorectal cancer. The effects of the histone deacetylase inhibitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
36
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 31 publications
11
36
0
Order By: Relevance
“…In the present study, the co-administration of VPA with PI, MG132, PI-1 or PR-39 induced a marked increase in apoptosis in human colorectal cancer cells. Our results are consistent with those reported by other groups using several different cell systems and various combinations of HDACIs and PIs (1,15,22,35,39).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In the present study, the co-administration of VPA with PI, MG132, PI-1 or PR-39 induced a marked increase in apoptosis in human colorectal cancer cells. Our results are consistent with those reported by other groups using several different cell systems and various combinations of HDACIs and PIs (1,15,22,35,39).…”
Section: Discussionsupporting
confidence: 93%
“…In cell culture models, HDAC inhibitors (HDACIs) have been shown to decrease proliferation rates, induce apoptosis and induce autophagy-related cell death in several cancer cell lines. Due to their relative specificity toward cancer cells, HDACIs represent a new class of cancer treatment agents that are generally well tolerated (1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under such stress conditions, that is, during inflammation, the expression of proteasome proteins might be enhanced in a Nrf2-dependent manner, accounting for increased proteasome activity and UPP-mediated survival and growth of colon cancer cells. In line with this notion, very recent studies revealed that proteasome inhibition or knockdown of certain proteasomal subunit proteins impair the growth and survival of colorectal cancer cells (Chen et al, 2009;Pitts et al, 2009). Nuclear factor E2-related factor 2 (Nrf2)-induced S5a and a-5 expression in colon epithelial cells confers protection from tumor necrosis factor-related apoptosis-inducing ligand (TRAIL)-induced apoptosis.…”
Section: Discussionmentioning
confidence: 97%
“…Accordingly, proteasome inhibition has meanwhile become a valuable and powerful tool in the treatment of certain types of cancer (Almond and Cohen, 2003;Goy et al, 2003;Adams, 2004); yet, other tumor entities turned out to be rather resistant to proteasome inhibitors. Nevertheless, recent studies (Chen et al, 2009;Pitts et al, 2009) showed that proteasome inhibition might also be effective for the treatment of colon cancer.…”
Section: Introductionmentioning
confidence: 99%